The master puppeteer - Paterson, Katherine; Wells, Haru (New York : Crowell, 1975)
A thirteen-year-old boy describes the poverty and discontent of eighteenth century Osaka and the world of puppeteers in which he lives.
School Library Journal.
Wilson's Junior High School.
7.3
7.6
5-8.
Young Adult
Keywords: Puppets -- Fiction; Puppets and puppet plays -- Fiction; Japan -- Fiction; Japan -- History -- Fiction